PENGOLAHAN SAMPAH RUMAH TANGGA BERBASIS 3R BERDAYA GUNA EKONOMI DI KSM PAGUNTAKA KOTA TARAKAN - Banyuriatiga, Banyuriatiga; Prasetyo, Andri Yogi Adyatma; Sari, Nove Kurniati; Chairiyah, Nurul; Adiwena, Muh. (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
Household waste management has become a significant challenge in maintaining environmental cleanliness and improving community welfare. This community service program aims to implement waste processing based on the 3R principles (Reduce, Reuse, Recycle) with added economic value in the Community Self-Help Group (KSM) Paguntaka, Tarakan City. The activities include education, training, and mentoring in managing organic waste. Organic waste is processed into compost using a simple fermentation method.. The program's results indicate an increase in community understanding of the 3R concept and the ability to process waste into economically valuable products. Furthermore, additional income from the sale of recycled products has contributed to improving the welfare of KSM members. This program also positively impacts reducing the volume of waste that ends up in the landfill, thus supporting environmental conservation efforts. In conclusion, the 3R-based waste management approach involving community empowerment has proven effective in generating economic and environmental benefits. This program is expected to be replicated in other communities to support sustainable waste management.